THE EFFECT OF WORK FROM HOME, WORK MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE - Infantri, Charis Bustanul; Ginting, Ginta; Asih, Daru (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
This research aims to determine the effect of Work from Home (WFH) and work motivation on employee performance mediated by job satisfaction, as well as determine the role of gender in moderating the relationship between WFH and employee performance. This research is quantitative research with a causality analysis approach. The research instrument used was a questionnaire prepared on a five-point Likert scale. The sample size in this study was 293 respondents, all of whom were employees of the Tanjung Priok Main Service Office of Type A Customs and Excise. Data were analyzed using the SEM-PLS method with the help of SmartPLS software version 3.2.29. The research results show that WFH has a positive and significant effect on job satisfaction and employee performance. Work motivation has a positive and significant effect on job satisfaction, but had no significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. Job satisfaction can partially mediate the relationship between WFH and employee performance, as well as fully mediate the relationship between work motivation and employee performance. Gender can strengthen the effect of Work from Home (WFH) on employee performance, especially for female employees.